POPULATION MIGRATION AND SETTLEMENT STRUCTURAL MOVEMENTS IN THE REPUBLIC OF ARMENIA (2002–2015) (Proceedings of the YSU C: Geological and Geographical Sciences, 2017)
The migration and resettlement questions in RA are discussed in the article. The population migration ratio of different settlements and their changes during 2002 till 2015 are calculated also, as well as the structural and territorial movements due to migration in RA are discussed. One can find different suggestions, which concern the productive interaction between migration and resettlement.
Keywords: migration; settlement; demographic situation; settlement pattern; urbanization